TEKNOLOGI KOMUNIKASI DAN INFORMASI MELALUI WEBSITE SEBAGAI STRATEGI PROMOSI KEBUDAYAAN DAN PARIWISATA PROPINSI MALUKU UTARA (Suatu Tinjauan Dari Perspektif Ilmu Komunikasi) - Lisda Ariani Simabur; Suyatno Kahar (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The results showed that; 1) The concept of the message on disbudpar.malutprov.go.id website owned by the North Maluku Province Tourism Office that is promoting the culture and tourism in North Maluku and informing the promotion activities to the community/the intended destination about what will be found in visiting the disbudpar website malutprov.go.id. 2) Constraints faced are the limitations of human resources (HR) in the management of the website disbudpar.malutprov.go.id, the problem of internet network that are problematic and not too adequate in the office so that it becomes an obstacle, and also regarding the allocation of funding or budget that is still not maximum as supporting the maintenance costs of server equipment and financing of internet quota at the office, as well as the lack of coordination channels between the Tourism Office and the Regency/City Tourism Office that have not been effective in the content promotion message content on the website disbudpar.malutprov.go.id. 3) The response of visitors to the website disbudpar.malutprov.go, namely the design and appearance is very simple so that it is easy to understand when opening the website, and some representations of images displayed also attract the attention of the end to see the objects of tourist destinations in North Maluku.